KETERAMPILAN COLLABORATIVE PROBLEM SOLVING SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA - Khoirun Nisa; Tatag Yuli Eko Siswono; Rooselyna Ekawati (LPPM Universitas Bina Bangsa, 2023)
This study is descriptive research that aims to describe students' collaborative problem solving (CPS) skills in solving mathematics problems. The subjects in this study were 6 students at grade XI consisting of 2 students with high mathematical abilities, 2 students with moderate mathematical abilities, and 2 students with low mathematical abilities. The six of them were divided into 3 groups consisting of 2 students with different mathematical abilities. The three groups were given mathematics problems to be solved collaboratively. The results of this study were analyzed using the semiotic Peirce model approach which uses a trichotomous relationship between representamen (Z), interpretant (I), and object (O) to show the CPS process that occurs. The results of the study show that students' CPS skills vary. The CPS process of high and moderate mathematical ability students is running quite well. Meanwhile, the CPS process of high and low mathematical ability students and moderate and low mathematical ability students was not as good as expected because of the little interaction or discussion between the members of the group in solving problems